2008
DOI: 10.1038/ijo.2008.113
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and ‘eating in the absence of hunger’ in children

Abstract: EAH is a behavioural phenotype that is not specific to overweight children but instead shows a graded association with adiposity across the weight continuum, particularly in boys. In this study, the effect was less pronounced in girls, which may reflect social desirability pressures constraining food intake among heavier girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
103
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(124 citation statements)
references
References 28 publications
14
103
4
Order By: Relevance
“…The results of this study align with previous work in older children reporting that EAH increases with age 5,6,[9][10][11]15 and is associated with increased adiposity. [4][5][6][7][8][9][10][11][12][13][14][15] The results also align with work in infants showing that parent-reported greater food responsiveness predicts greater prospective weight gain from ages 3 to 15 months. 34 Although older children showed positive affect at food presentation, this positive affect was not associated with greater BMIz at 33 months.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of this study align with previous work in older children reporting that EAH increases with age 5,6,[9][10][11]15 and is associated with increased adiposity. [4][5][6][7][8][9][10][11][12][13][14][15] The results also align with work in infants showing that parent-reported greater food responsiveness predicts greater prospective weight gain from ages 3 to 15 months. 34 Although older children showed positive affect at food presentation, this positive affect was not associated with greater BMIz at 33 months.…”
Section: Discussionsupporting
confidence: 76%
“…1 The continued consumption of foods past satiety, referred to as eating in the absence of hunger (EAH), 2 is correlated with greater food responsiveness and enjoyment, and less satiety responsiveness, 3 as well as greater adiposity. [4][5][6][7][8][9][10][11][12][13][14][15] Interventions that reduce responsiveness to food cues [16][17][18] have been shown to reduce EAH, but interventions that increase children's awareness of hunger and satiety cues had no effect. 16 Thus, EAH may primarily reflect food enjoyment and responsiveness as opposed to sensitivity to hunger and satiety cues.…”
mentioning
confidence: 99%
“…Indeed, certain studies have found that associations between selfregulatory eating measures and overweight status or obesity risk differ by child sex. 49,50 All analyses used two-tailed significance tests with a ¼ 0.05. The Statistical Package for the Social Sciences (SPSS, Version 16, Chicago, IL, USA) was used for all analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Of special interest here is 'eating in the absence of hunger' (EAH). As a behavioral measure of disinhibition, EAH reflects the tendency to consume large amounts of appealing foods in a short time, irrespective of hunger (Hill et al 2008). EAH research is grounded in Schachter's (1968) early findings that obese people are more sensitive than others to food cues in the environment.…”
Section: ___________________mentioning
confidence: 99%